La autoridad : verla en televisión y vivirla en familia (2017)
ABSTARCT: This analytical paper shares results from a hermeneutical study that aims to understand the meaning placed on representations of authority on television among parents and their children. Participants in the study come from different social and economic levels in the cities of Medellín and Envigado, Colombia. The research focuses on the cultural role of television in shaping intergenerational relationships. Interviews and focal groups were conducted by the authors, identifying that television shows a childish autonomous world governed by its own rules and equal relationships between adults and children, which go against the actual hierarchy of the family life. Despite the high number of hours that people watch, television is not shown to be an intermediary for parental authority, which disputes the technocentric position that is attributed to this form of mass mediaRESUMEN: Este artículo de carácter analítico presenta resultados de una investigación hermenéutica cuyo objetivo fue comprender el sentido que le otorgan padres, madres, niños y niñas de distintos estratos socioeconómicos de Medellín y Envigado a las representaciones de autoridad agenciadas por la televisión. Los alcances de la investigación se orientan a desentrañar el papel cultural de la televisión en la configuración de las relaciones intergeneracionales. Se realizaron entrevistas y grupos focales y se halló que la televisión muestra un mundo infantil autonomizado definido por sus propias normas y relaciones igualitarias entre adultos y niños en contravía de las jerárquicas de la vida familiar. A pesar de su alto consumo, la televisión no es una mediación para la autoridad parental lo que replantea la postura tecnocéntrica adjudicada al medio.